INTERACTION DESIGN FOR WEB CV SCREENING SYSTEM - Stefanny
This final research project undertakes the design of a web-based CV screening system with a user-centered design (UCD) approach based on the ISO 9241-210 standard. It creates a highfidelity prototype that aligns with user and stakeholder needs. The resulting prototype serves as a foundation for the development of the CV screening system by frontend, backend, and machine learning developers. The analysis of user requirements generates hypotheses for essential features in the recruitment process. These include job description and qualifications input, candidate CV uploading and downloading, candidate communication, and other features influencing the user experience. Testing of the prototype occurs through two remote iterations involving seven participants. The goal is to evaluate goals of usefulness, effective usage, efficiency, and learnability of the system. Test results demonstrate that the high-fidelity prototype's features meet user needs in the CV screening process. Users are able to effectively utilize the system with a 100% success rate, and there's a 39.1% efficiency enhancement in the second round of testing. The system is also perceived as easy to learn, with an SEQ score of 6.96 out of 7, indicating successful provision of an easily understandable user experience. Overall, the testing outcome verifies that the design fulfills user needs in the CV screening process. Based on the testing results, crucial interaction design features are those features hypothesized during the user requirement analysis phase. The interaction design effectively addresses the HR division's needs in the CV screening process.